The adjunctive use of a controlled-release chlorhexidine chip following treatment with a new ultrasonic device in supportive periodontal therapy: a prospective, controlled clinical study - Adrian Kasaj (Journal compilation 2007 Blackwell Munksgaard, 2007)
The aim of this randomised, splitmouth, controlled clinical trial was to evaluate the effectiveness of a controlled-release chlorhexidine chip (CHX chip) as an adjunctive therapy to scaling and root planing (SRP) with a newly developed ultrasonic device in supportive periodontal therapy (SPT).